2020
DOI: 10.3390/pathogens9060482
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Prion Protein Isoforms Are Not Present in Cerebral Organoids Generated from Asymptomatic Donors Carrying the E200K Mutation Associated with Familial Prion Disease

Abstract: Cerebral organoids (COs) are a self-organizing three-dimensional brain tissue mimicking the human cerebral cortex. COs are a promising new system for modelling pathological features of neurological disorders, including prion diseases. COs expressing normal prion protein (PrPC) are susceptible to prion infection when exposed to the disease isoforms of PrP (PrPD). This causes the COs to develop aspects of prion disease pathology considered hallmarks of disease, including the production of detergent-insoluble, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 37 publications
(56 reference statements)
3
30
0
Order By: Relevance
“…While we have previously shown that COs can model infectious prion disease, we and others also found that COs generated from donors with the E200K mutation within the prion protein gene ( PRNP ) that causes genetic CJD do not show any parameters of disease [ 6 , 19 ]. To investigate whether the PRNP E200K mutation can influence electrophysiological functions of the CO cultures and contrast this with the trisomy 21-causing AD and LRRK2 G2019S -causing PD mutations, organoids at 3–4 and 6–10 months post differentiation were monitored for electrophysiological aberrations and for changes in their synaptic receptors.…”
Section: Introductionmentioning
confidence: 99%
“…While we have previously shown that COs can model infectious prion disease, we and others also found that COs generated from donors with the E200K mutation within the prion protein gene ( PRNP ) that causes genetic CJD do not show any parameters of disease [ 6 , 19 ]. To investigate whether the PRNP E200K mutation can influence electrophysiological functions of the CO cultures and contrast this with the trisomy 21-causing AD and LRRK2 G2019S -causing PD mutations, organoids at 3–4 and 6–10 months post differentiation were monitored for electrophysiological aberrations and for changes in their synaptic receptors.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that interactions between host genetics and cellular environment trigger the conversion of PrP to PrP Sc [16][17][18]. Our group has previously found that hCOs produced from asymptomatic donors carrying the PrP gene (PRNP) E200K mutation do not develop any signs of PrD up to 12 months post-differentiation [16].…”
Section: Organoids Allow Study Of Prnp Mutations and Cellular Triggers Of Prion Conversionmentioning
confidence: 99%
“…However, using hCOs, treatment can be tested against any subtype in large numbers. Additionally, iPSCs can be derived from skin samples making patient-specific COs easily obtainable for personalized testing [16]. Furthermore, PRNP mutations introduced through CRISPR/Cas-9 technology can generate larger numbers of individual iPSC cell lines than can be obtained from donors with the advantage of isotype controls.…”
Section: Infected Organoids Are Responsive To Anti-prion Compoundsmentioning
confidence: 99%
“…Foliaki et al, prepared organoids from the fibroblasts of 2 people carrying the E200K CJD mutation, which is the most common familial prion disease mutation. Despite a line of transgenic mouse model with this mutation developing disease at about 5-6 months old [ 117 ], neither organoid showed any sign of PrP seeding activity or pathology after culturing for 12 months [ 118 ]. Again, this illustrates the difference between transgenic mice and humans, and also the need to identify methods of inducing or accelerating familial prion disease in organoids.…”
Section: Organoidsmentioning
confidence: 99%